Positive electrode active material, positive electrode, and lithium secondary battery

JP2026165105APending Publication Date: 2026-10-13SAMSUNG SDI CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2026052858
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2026-03-20
Filing Date
2026-03-26
Publication Date
2026-10-13

AI Technical Summary

Benefits of technology

【0010】 一実施形態による正極活物質は、平均粒径の異なる3種類の正極活物質を特定の重量比で含むことによって、粉体流動性が改善されペレット密度が増加し主応力が減少できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026165105000001_ABST
    Figure 2026165105000001_ABST
Patent Text Reader

Abstract

The present invention provides a positive electrode active material in which powder flowability is improved, pellet density is increased, and principal stress is reduced; a positive electrode containing the positive electrode active material in which resistance is reduced while further improving energy density and efficiency; and a lithium secondary battery. [Solution] The positive electrode active material has an average particle size (D 50 The first positive electrode active material has a particle size of 10 μm or more and 30 μm or less, and contains a first lithium nickel-based composite oxide, with an average particle size (D 50 The second positive electrode active material has a particle size of 5 μm or more and less than 10 μm and contains a second lithium nickel-based composite oxide, and the average particle size (D 50 The positive electrode active material includes a third positive electrode active material containing a third lithium nickel-based composite oxide, wherein the particle size is 0.1 μm or more and less than 5 μm, the combined weight of the second positive electrode active material and the third positive electrode active material is more than 20% by weight and less than 40% by weight based on the total weight of the positive electrode active material, and the powder fluidity of the positive electrode active material is 4.2 or higher.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This relates to positive electrode active materials, positive electrodes, and lithium secondary batteries. [Background technology]

[0002] Lithium-ion batteries, which offer high energy density while being easily portable, are primarily used as power sources for mobile information terminals such as mobile phones, laptops, and smartphones. Recently, research has been actively conducted on using high-energy-density lithium-ion batteries as power sources or energy storage sources for hybrid and electric vehicles.

[0003] To realize lithium secondary batteries that meet these applications, a variety of positive electrode active materials are being considered. Among them, lithium nickel-based composite oxides (e.g., lithium nickel manganese cobalt oxide, lithium nickel cobalt aluminum oxide, etc.), lithium cobalt oxide, and lithium iron phosphate compounds are used as positive electrode active materials.

[0004] Of these, lithium nickel-based composite oxides can achieve high energy density and have been actively developed recently. However, the capacity of lithium nickel-based composite oxides varies depending on the particle size and morphology. Therefore, bimodal cathode active materials, which are a mixture of large and small particles, are used. However, in the case of such bimodal cathode active materials, the powder flowability is poor, which limits the achievement of high energy density and high efficiency. [Overview of the project] [Problems that the invention aims to solve]

[0005] One embodiment aims to provide a positive electrode active material in which powder flowability is improved, pellet density is increased, and principal stress is reduced.

[0006] Another embodiment aims to provide a positive electrode and lithium secondary battery that include the positive electrode active material, thereby reducing resistance while further improving energy density and efficiency. [Means for solving the problem]

[0007] According to one embodiment, the average particle size (D 50 The particle size is 10 μm to 30 μm and the first positive electrode active material contains a first lithium nickel-based composite oxide, with an average particle size (D 50 The second positive electrode active material has a particle size of 5 μm or more and less than 10 μm and contains a second lithium nickel-based composite oxide, and the average particle size (D 50 A positive electrode active material is provided, comprising a third positive electrode active material containing a third lithium nickel-based composite oxide, wherein the particle size is 0.1 μm or more and less than 5 μm, the combined weight of the second positive electrode active material and the third positive electrode active material is more than 20% by weight and less than 40% by weight based on the total weight of the positive electrode active material, and the powder flow function (FF) of the positive electrode active material is 4.2 or higher.

[0008] According to another embodiment, a positive electrode is provided, comprising a positive electrode current collector and a positive electrode active material layer located on the positive electrode current collector and containing the positive electrode active material.

[0009] Another embodiment provides a lithium secondary battery comprising the aforementioned positive electrode, negative electrode, and electrolyte. [Effects of the Invention]

[0010] In one embodiment, the positive electrode active material contains three types of positive electrode active materials with different average particle sizes in a specific weight ratio, thereby improving powder flowability, increasing pellet density, and reducing principal stress.

[0011] The positive electrode and lithium secondary battery containing the aforementioned positive electrode active material can achieve high energy density and high efficiency. [Brief explanation of the drawing]

[0012] [Figure 1]This figure schematically shows a lithium secondary battery according to one embodiment. [Figure 2] This figure schematically shows a lithium secondary battery according to one embodiment. [Figure 3] This figure schematically shows a lithium secondary battery according to one embodiment. [Figure 4] This figure schematically shows a lithium secondary battery according to one embodiment. [Modes for carrying out the invention]

[0013] The following describes specific embodiments in detail so that they can be easily implemented by those with ordinary skill in the art. However, the present invention can be realized in a variety of different forms and is not limited to the embodiments described herein.

[0014] The terms used herein are for illustrative purposes only and are not intended to limit the invention. Unless otherwise clearly stated in the context, singular expressions include plural expressions.

[0015] Here, "these combinations" refers to mixtures of components, laminates, composites, copolymers, alloys, blends, reaction products, etc.

[0016] Here, terms such as “include,” “equip,” or “possess” are intended to specify the existence of the implemented features, figures, stages, components, or combinations thereof, and should be understood not to preemptively exclude the existence or possibility of adding one or more other features, figures, stages, components, or combinations thereof.

[0017] To clearly represent various layers and regions in the drawings, thicknesses are shown enlarged, and similar parts are given the same drawing reference numerals throughout the specification. When a layer, film, region, plate, or other part is said to be "on top of" or "on" another part, this includes not only when it is "directly on top of" another part, but also when there is another part in between. Conversely, when a part is said to be "directly on top of" another part, it means that there is no other part in between.

[0018] Furthermore, the term "layer" here includes not only the shapes formed on the entire surface when observed in a plan view, but also the shapes formed on a portion of the surface.

[0019] The average particle size can be measured by methods widely known to those skilled in the art, for example, by a particle size analyzer, or by transmission electron microscope images or scanning electron microscope images. Alternatively, it can be measured using dynamic light scattering, and after performing data analysis and counting the number of particles for each particle size range, the average particle size value can be calculated from this. Unless otherwise defined, the average particle size (D 50 ) can mean the diameter of the particle whose cumulative volume in the particle size distribution is 50% by volume. Also, unless otherwise defined, the average particle size is obtained by measuring the size (diameter or length of the major axis) of more than 20 random particles in a scanning electron microscope image to obtain a particle size distribution, and the diameter of the particle whose cumulative volume in the said particle size distribution is 50% by volume is defined as the average particle size (D 50 It is also acceptable to take it as ).

[0020] Here, "or" is not interpreted as having an exclusive meaning; for example, "A or B" is interpreted as including A, B, A+B, etc.

[0021] The term "metal" is interpreted as encompassing general metals, transition metals, and metalloids.

[0022] positive electrode active material The positive electrode active material according to one embodiment has an average particle size (D 50The particle size is 10 μm or more and 30 μm or less, and the first positive electrode active material contains a first lithium nickel-based composite oxide, and the average particle size (D 50 The particle size is 5 μm or more and less than 10 μm, and the second positive electrode active material contains a second lithium nickel-based composite oxide, and the average particle size (D 50 The particle size is 0.1 μm or more and less than 5 μm, and the cathode active material contains a third lithium nickel composite oxide, the combined weight of the second cathode active material and the third cathode active material is more than 20% by weight but less than 40% by weight based on the total weight of the cathode active material, and the powder flow function (FF) of the cathode active material is 4.2 or higher.

[0023] To achieve high energy density, lithium nickel-based composite oxide cathode active materials with high specific capacity are primarily used. When using lithium nickel-based composite oxides, the repeated volume expansion of the crystal structure as the charge-discharge cycle progresses causes the gaps between primary particles to widen and the arrangement of primary particles to shift. This leads to increasingly greater contraction and expansion of secondary particles and the cathode containing them. This can cause structural cracks and fractures in the secondary particles and cathode, inducing a disruption in the electrochemical charge transfer network and causing charge imbalance. Furthermore, the increased side reaction area with the electrolyte can lead to a deterioration of the repeated charge-discharge cycle life.

[0024] To address the aforementioned problems, various studies are ongoing to mitigate the volume change of lithium nickel-based composite oxides after repeated charging and discharging, or to minimize the stress generated by volume changes, thereby preventing particle damage.

[0025] To increase capacity, a bimodal type positive electrode active material is used, which is a mixture of small and large particles with different average particle sizes. In such a bimodal type positive electrode active material, the gaps between the large particles can be filled by the small particles with relatively smaller average particle sizes, improving the accumulation density of lithium nickel-based composite oxide per unit volume and increasing the energy density per unit volume. However, even when using a bimodal form of positive electrode active material, there is still the problem of low powder fluidity. Here, powder fluidity is a physical property that indicates the ability of the powder to move. The lower the powder fluidity, the smaller the inter-particle contact section, which can result in high resistance during battery evaluation, particle cracking when pressure is applied, and a low inter-particle void filling rate.

[0026] The inventors of this application propose a tri-modal type positive electrode active material with high powder fluidity, characterized by increased inter-particle contact sections, lower resistance, and, when pressure is applied, less particle movement and instead of particles breaking, particle filling of the inter-particle voids. The tri-modal type positive electrode active material is a mixture of three types of positive electrode active materials with different average particle sizes in a specific ratio, and may be a mixture of small, medium, and large particles. The tri-modal type positive electrode active material has increased pellet density, reduced principal stress, and superior powder fluidity compared to existing bimodal type positive electrode active materials. As a result, positive electrodes and lithium secondary batteries containing the tri-modal type positive electrode active material can further improve energy density and efficiency compared to those containing bimodal type positive electrode active materials, while reducing resistance.

[0027] In particular, by adjusting the content of medium particles (second positive electrode active material) and small particles (third positive electrode active material) in the trimodal form to the aforementioned range (total weight is more than 20% by weight but less than 40% by weight based on the total weight of the positive electrode active material), the pellet density can be further increased, the principal stress can be further reduced, and the powder flowability can be further improved compared to not only the bimodal form of positive electrode active material but also to the trimodal form of positive electrode active material that does not satisfy the aforementioned specific content range. For example, the combined weight of the second positive electrode active material and the third positive electrode active material may be 21% to 39% by weight, 22% to 38% by weight, 23% to 37% by weight, 24% to 36% by weight, 25% to 35% by weight, 26% to 34% by weight, 28% to 32% by weight, or 30% by weight based on the total weight of the positive electrode active material. On the other hand, if the combined weight of the second positive electrode active material and the third positive electrode active material deviates from the range, the pellet density of the positive electrode active material may decrease, and / or the principal stress may increase, and / or the powder fluidity may decrease.

[0028] The powder flowability of the positive electrode active material may be, for example, 4.2-5.5, 4.25-5.3, 4.3-5.2, 4.35-5.1, 4.4-5, 4.45-4.9, or 4.45-4.85. The powder flowability of the positive electrode active material can be measured using an FT4 Powder Rheometer (Freeman Technology). Specifically, 200 ml of the positive electrode active material can be placed in a 300 ml container (vessel), the container can be fixed to the apparatus, and the measurement can be taken at 9 kPa while moving the blade counterclockwise at a speed of 100 mm / s. The measurement may be repeated a total of three times and the average value calculated. In this case, the powder flowability may be the average powder flowability. In this case, the powder flowability may be a flow function (FF) value calculated based on the flow resistance of the powder particles generated when the blade passes through the powder layer. The above flow function (FF) is defined as the value obtained by dividing the major principal stress (σ1) by the unconfined yield strength (σc) of the powder, as shown in Equation 1 below, and may be a dimensionless value that indicates the flow characteristics of the powder. The positive electrode active material is a trimodal type containing the above-mentioned large-grained first positive electrode active material, medium-grained second positive electrode active material, and small-grained third positive electrode active material in a specific content ratio, and may have excellent powder flowability as the powder flow rate satisfies the above range. A positive electrode containing positive electrode active material that satisfies the above powder flow rate range can increase the composite density, and a lithium secondary battery containing the positive electrode can have improved initial charge / discharge capacity and efficiency, a significant decrease in DC-IR, and improved resistance. [Formula 1] FF = σ1 / σc Here, σ1 represents the major principal stress when the powder is in a compressed state, and σc may represent the unconfined yield strength at which the powder begins to collapse without external constraints.

[0029] The positive electrode active material may have a pellet density of 3.6 g / cc to 4 g / cc, for example, 3.6 g / cc to 3.9 g / cc, 3.6 g / cc to 3.8 g / cc, or 3.6 g / cc to 3.7 g / cc. The pellet density of the positive electrode active material may be measured after pressurizing 3 g of the positive electrode active material at a pressure of 5 tons for 30 seconds. The pellet density within the aforementioned range can be achieved by including the first positive electrode active material, the second positive electrode active material, and the third positive electrode active material in specific weight ratios. When the pellet density of the positive electrode active material satisfies the aforementioned range, the positive electrode active material can be densely packed, and the capacity of the positive electrode containing it can be increased. Furthermore, a lithium secondary battery containing such a positive electrode can have reduced resistance while further improving energy density and efficiency. The pellet density can be measured from the pellet thickness and mold diameter after placing 3 g of the positive electrode active material in a pellet manufacturing mold and maintaining it at 5 tons for 30 seconds.

[0030] The principal stress of the positive electrode active material may be 20 kPa or less, and may be, for example, 19 kPa or less, 18 kPa or less, 17 kPa or less, 16 kPa or less, 15 kPa or less, 14 kPa or less, or 13.6 kPa or less. For example, the principal stress of the positive electrode active material may be 1 kPa to 20 kPa, 2 kPa to 20 kPa, 3 kPa to 20 kPa, 5 kPa to 20 kPa, 6 kPa to 20 kPa, 8 kPa to 20 kPa, 9 kPa to 20 kPa, 10 kPa to 19 kPa, or 12 kPa to 19 kPa. The principal stress refers to the value obtained by measuring the force that resists when an external force or moment is applied to the positive electrode active material and dividing this by the unit area. When the principal stress is high, it means that the coefficient of friction increases, and when the coefficient of friction increases, the ability of particles to move decreases, which is disadvantageous in terms of density, and this can mean that the energy density decreases. The positive electrode active material according to one embodiment has a low principal stress, as described above, and therefore can be packed to a high density. The principal stress of the positive electrode active material can be measured using a powder shear tester, for example, using a shear cell or a powder rheology analyzer. As an example, the principal stress of the positive electrode active material can be measured using an FT4 Powder Rheometer (Freeman Technology). Specifically, the principal stress can be measured at 9 kPa by filling a 300 ml container (vessel) with 200 ml of the positive electrode active material, fixing the container to the apparatus, and moving the blade counterclockwise at a speed of 100 mm / s. The measurement may be repeated a total of three times and the average value may be calculated. In this case, the principal stress may be the average principal stress. When the principal stress of the positive electrode active material satisfies the aforementioned range, the particles within the positive electrode active material can move relatively freely, meaning that the powder fluidity is high. This results in a positive electrode with low resistance, less particle cracking under pressure, and high stability, thereby improving the performance of the lithium secondary battery containing the positive electrode.

[0031] The first positive electrode active material, the second positive electrode active material, and the third positive electrode active material will be described in detail below.

[0032] First positive electrode active material The first positive electrode active material has an average particle diameter (D 50 ) of 10 μm to 30 μm, and includes a first lithium-nickel-based composite oxide. Here, the numerical range expressed as "x μm to y μm" means a value equal to or greater than x μm and equal to or less than y μm, and the same applies hereinafter regardless of the unit of the numerical value. The first positive electrode active material can also be referred to as large particles or large grains.

[0033] The first positive electrode active material may be in a particle form, or may be in a form of secondary particles in which a plurality of primary particles are aggregated. The average particle diameter (D 50 ) of the first positive electrode active material may be the average particle diameter (D 50 ) of the secondary particles.

[0034] The average particle diameter (D 50 ) of the first positive electrode active material may be, for example, 10 μm to 25 μm, 10 μm to 20 μm, 10 μm to 15 μm, 11 μm to 14 μm, or 11.5 μm to 13.5 μm. Here, the average particle diameter (D 50 ) may be obtained by randomly measuring the size (diameter or major axis length) of more than 20 particles in a scanning electron microscope image of the first positive electrode active material in the positive electrode active material to obtain a particle size distribution, and taking the diameter of particles with a cumulative volume of 50% by volume in the particle size distribution as the average particle diameter.

[0035] The first lithium-nickel-based composite oxide, the second lithium-nickel-based composite oxide, and the third lithium-nickel-based composite oxide may be the same as or different from each other. As an example, the first lithium-nickel-based composite oxide, the second lithium-nickel-based composite oxide, and the third lithium-nickel-based composite oxide may differ only in average particle diameter (D 50 ) and have exactly the same composition, or two of the three types of particles may have the same composition, the remaining one type of particle may have a different composition, or all three types of particles may have compositions different from each other.

[0036] The first lithium nickel-based composite oxide can be represented by the following chemical formula 1.

[0037] [Chemical formula 1] Li a1 Ni x1 M 1 y1 M 2 z1 O 2-b1 X b1 In chemical formula 1, 0.9 ≤ a1 ≤ 1.8, 0.3 ≤ x1 ≤ 1, 0 ≤ y1 ≤ 0.7, 0 ≤ z1 ≤ 0.7, 0.9 ≤ x1 + y1 + z1 ≤ 1.1, and 0 ≤ b1 ≤ 0.1, M 1 and M 2 These are all distinct elements, each independently of the others being Al, B, Ba, Ca, Ce, Co, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sn, Sr, Ta, Ti, V, W, Y, Zn, Zr, or any combination thereof, while X is F, P, S, or any combination thereof.

[0038] In chemical formula 1, 0.6 ≤ x1 ≤ 1, 0 ≤ y1 ≤ 0.4, and 0 ≤ z1 ≤ 0.4, or 0.8 ≤ x1 ≤ 1, 0 ≤ y1 ≤ 0.2, and 0 ≤ z1 ≤ 0.2, or 0.9 ≤ x1 < 1, 0 <y1≦0.1、および0≦z1≦0.1であってもよい。

[0039] The first lithium nickel-based composite oxide can be represented by the following chemical formula 11 or chemical formula 12 as a specific example.

[0040] [Chemical formula 11] Li a11 Ni x11 Co y11 M 11 z11 O 2-b11 X b11 In chemical formula 11, 0.9≦a11≦1.2, 0.8≦x11<1, 0 <y11≦0.2、0≦z11≦0.2、0.9≦x11+y11+z11≦1.1、および0≦b11≦0.1であり、M 11X is Al, B, Ba, Ca, Ce, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sn, Sr, Ta, Ti, V, W, Y, Zn, Zr, or a combination thereof, and X is F, P, S, or a combination thereof.

[0041] In chemical formula 11, 0.9 ≤ x 11 ≤ 0.99, 0.01 ≤ y 11 ≤ 0.1, and 0 ≤ z 11 ≤ 0.1 may also be applied.

[0042] [Chemical formula 12] Li a12 Ni x12 Co y12 M 12 z12 M 13 w12 O 2-b12 X b12 In chemical formula 12, 0.9≦a12≦1.2, 0.8≦x12≦0.98, 0.01≦y12≦0.19, 0.01≦z12≦0.19, 0≦w12≦0.19, 0.9≦x12+y12+z12+w12≦1.1, and 0≦b12≦0.1, M 12 is Al, Mn, or a combination thereof, M 13 These are B, Ba, Ca, Ce, Cr, Cu, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ta, Ti, V, W, Y, Zn, Zr, or combinations thereof, M 12 and M 13 These are all different elements, and X is F, P, S, or a combination of these.

[0043] In chemical formula 12, 0.9 ≤ x 12 ≤ 0.98, 0.01 ≤ y 12 ≤ 0.09, 0.01 ≤ z 12 ≤ 0.09, and 0 ≤ w 12 ≤ 0.09 may also be used.

[0044] In the first lithium-nickel composite oxide, the nickel content may be 80 mol% or more with respect to 100 mol% of the metal excluding lithium, for example, 82 mol% or more, 85 mol% or more, 87 mol% or more, 90 mol% or more, or 91 mol% or more, or 99 mol% or less, for example, 95 mol% or less, and may be a high-nickel positive electrode active material. High-nickel positive electrode active materials can achieve high capacity and can be applied to high-capacity, high-density lithium secondary batteries.

[0045] The first positive electrode active material may be included in an amount exceeding 60% by weight but less than 80% by weight based on the total weight of the positive electrode active material, for example, in amounts of 62% to 78% by weight, 64% to 76% by weight, 65% to 75% by weight, 66% to 74% by weight, 68% to 72% by weight, or 70% by weight. The content of the first positive electrode active material may also be the value obtained by subtracting the combined weight of the second and third positive electrode active materials from the total weight of the positive electrode active material. When the weight of the first positive electrode active material satisfies the above range, the pellet density of the positive electrode active material increases, the principal stress decreases, and the powder flowability can increase. On the other hand, when the content of the first positive electrode active material deviates from the above range, the pellet density may decrease and / or the principal stress may increase and / or the powder flowability may decrease.

[0046] Second positive electrode active material The second positive electrode active material has an average particle size (D 50 The second cathode active material has a particle size of 5 μm or more and less than 10 μm, and contains a second lithium nickel-based composite oxide. The second cathode active material can be described as having medium grains or medium particles. By including such a second cathode active material, the cathode active material according to one embodiment can achieve high capacity and high energy density while exhibiting improved lifetime characteristics.

[0047] The second positive electrode active material may be in particle form, for example, a secondary particle formed by the aggregation of multiple primary particles, or a single particle. Here, a single particle means a particle that exists alone without a grain boundary and consists of only one particle, and can mean a monolithic structure, a single-body structure, or a non-aggregated particle that exists as an independent phase in the morphology where particles do not aggregate with each other, and may be a single crystal as an example. The shape of the second positive electrode active material is not particularly limited and can have a variety of shapes such as polyhedra, spheres, ellipses, plates, rods, and amorphous shapes.

[0048] The average particle size (D) of the aforementioned second positive electrode active material 50 ) is the average particle size (D) of the aforementioned first positive electrode active material. 50 ) is smaller than the average particle size (D) of the third positive electrode active material described below. 50 ) is greater than the average particle size (D) of the second positive electrode active material. 50 The particle size (D) is 5 μm or more and less than 10 μm, for example, 5 μm to 9.5 μm, 5 μm to 9 μm, 5 μm to 8 μm, or 5 μm to 7 μm. Here, the average particle size (D) 50 ) may be obtained by measuring the size (diameter or length of the major axis) of more than 20 particles randomly in a scanning electron microscope image of the second positive electrode active material in the positive electrode active material to obtain a particle size distribution, and taking the diameter of the particle whose cumulative volume in the particle size distribution is 50 volume% as the average particle size. Here, if the second positive electrode active material is a secondary particle, the average particle size of the second positive electrode active material (D 50 ) is the average particle size of secondary particles (D 50 ) means that, if the second positive electrode active material is a single particle, the average particle size of the second positive electrode active material (D 50 ) is the average particle size (D 50 ) can mean.

[0049] According to one embodiment, the second positive electrode active material may be in the form of single particles, and the average particle size (D 50 ) is 5 μm or more and less than 10 μm.

[0050] The second lithium nickel-based composite oxide can be represented by the following chemical formula 2.

[0051] [Chemical formula 2] Li a2 Ni x2 M 3 y2 M 4 z2 O 2-b2 X b2 In chemical formula 2, 0.9 ≤ a² ≤ 1.8, 0.3 ≤ x² ≤ 1, 0 ≤ y² ≤ 0.7, 0 ≤ z² ≤ 0.7, 0.9 ≤ x² + y² + z² ≤ 1.1, and 0 ≤ b² ≤ 0.1, M 3 and M 4 These are all distinct elements, each independently of the others being Al, B, Ba, Ca, Ce, Co, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sn, Sr, Ta, Ti, V, W, Y, Zn, Zr, or any combination thereof, while X is F, P, S, or any combination thereof.

[0052] In chemical formula 2, either 0.6 ≤ x² ≤ 1, 0 ≤ y² ≤ 0.4, and 0 ≤ z² ≤ 0.4, or 0.8 ≤ x² ≤ 1, 0 ≤ y² ≤ 0.2, and 0 ≤ z² ≤ 0.2, or 0.9 ≤ x² < 1, 0 <y2≦0.1、および0≦z2≦0.1であってもよい。

[0053] The second lithium nickel-based composite oxide can be represented by the following chemical formula 21 or chemical formula 22 as a specific example.

[0054] [Chemical formula 21] Li a21 Ni x21 Co y21 M 21 z21 O 2-b21 X b21 In chemical formula 21, 0.9≦a21≦1.2, 0.8≦x21<1, 0 <y21≦0.2、0≦z21≦0.2、0.9≦x21+y21+z21≦1.1、および0≦b21≦0.1であり、M 21X is Al, B, Ba, Ca, Ce, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sn, Sr, Ta, Ti, V, W, Y, Zn, Zr, or a combination thereof, and X is F, P, S, or a combination thereof.

[0055] In chemical formula 21, 0.9 ≤ x²¹ ≤ 0.99, 0.01 ≤ y²¹ ≤ 0.1, and 0 ≤ z²¹ ≤ 0.1 may also be applied.

[0056] [Chemical formula 22] Li a22 Ni x22 Co y22 M 22 z22 M 23 w22 O 2-b22 X b22 In chemical formula 22, 0.9≦a22≦1.2, 0.8≦x22≦0.98, 0.01≦y22≦0.19, 0.01≦z22≦0.19, 0≦w22≦0.19, 0.9≦x22+y22+z22+w22≦1.1, and 0≦b22≦0.1, M 22 is Al, Mn, or a combination thereof, M 23 These are B, Ba, Ca, Ce, Cr, Cu, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ta, Ti, V, W, Y, Zn, Zr, or combinations thereof, M 22 and M 23 These are all different elements, and X is F, P, S, or a combination of these.

[0057] In chemical formula 22, 0.9 ≤ x²² ≤ 0.98, 0.01 ≤ y²² ≤ 0.09, 0.01 ≤ z²² ≤ 0.09, and 0 ≤ w²² ≤ 0.09 may also be used.

[0058] In the second lithium-nickel-based composite oxide, relative to 100 mol% of metals excluding lithium, the nickel content may be 80 mol% or more, for example, 82 mol% or more, 85 mol% or more, 87 mol% or more, 90 mol% or more, or 91 mol% or more, and may be 99 mol% or less, for example 95 mol% or less, which may be a high-nickel positive electrode active material. The high-nickel positive electrode active material can achieve high capacity, and can be applied to high-capacity, high-density lithium secondary batteries.

[0059] Third positive electrode active material The third positive electrode active material has an average particle diameter (D 50 ) of 0.1 μm or more and less than 5 μm, and includes a third lithium-nickel-based composite oxide. The third positive electrode active material may be expressed as small particles or fine particles.

[0060] The third positive electrode active material may be in a particulate form, and may be in the form of secondary particles formed by agglomeration of a plurality of primary particles, or a single particle. Here, the definition of the single particle is as previously described for the second positive electrode active material.

[0061] The average particle diameter (D 50 ) of the third positive electrode active material is smaller than the average particle diameter (D 50 ) of the second positive electrode active material. The average particle diameter (D 50 ) of the third positive electrode active material is 0.1 μm or more and less than 5 μm, and may be, for example, 0.1 μm to 4.5 μm, 0.1 μm to 4 μm, 0.1 μm to 3.5 μm, or 0.5 μm to 3 μm. Here, the average particle diameter (D 50 ) may be obtained by randomly measuring the sizes (diameters or major axis lengths) of more than 20 particles from a scanning electron microscope image of the third positive electrode active material in the positive electrode active material to obtain a particle size distribution, and taking the diameter of particles with a cumulative volume of 50% by volume in the particle size distribution as the average particle diameter.

[0062] Here, when the third positive electrode active material is secondary particles, the average particle diameter (D 50 ) of the third positive electrode active material is the average particle diameter (D 50) means that when the third positive electrode active material is a single particle, the average particle diameter D of the third positive electrode active material 50 ) may refer to the average particle diameter D of the single particle 50 ).

[0063] According to an embodiment, the third positive electrode active material may be in a single particle form, and the average particle diameter D of the single particle 50 ) is 0.1 μm or more and less than 5 μm.

[0064] The third lithium-nickel-based composite oxide may be represented by the following Chemical Formula 3.

[0065] [Chemical Formula 3] Li a3 Ni x3 M 5 y3 M 6 z3 O 2-b3 X b3 In Chemical Formula 3, 0.9≦a3≦1.8, 0.3≦x3≦1, 0≦y3≦0.7, 0≦z3≦0.7, 0.9≦x3+y3+z3≦1.1, and 0≦b3≦0.1, M 5 and M 6 are different elements, each independently selected from Al, B, Ba, Ca, Ce, Co, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sn, Sr, Ta, Ti, V, W, Y, Zn, Zr, or a combination thereof, and X is F, P, S, or a combination thereof.

[0066] In Chemical Formula 3, 0.6≦x3≦1, 0≦y3≦0.4, and 0≦z3≦0.4, or 0.8≦x3≦1, 0≦y3≦0.2, and 0≦z3≦0.2, or 0.9≦x3<1, 0<y3≦0.1, and 0≦z3≦0.1 may be satisfied.

[0067] The third lithium-nickel-based composite oxide may be represented by the following Chemical Formula 31 or Chemical Formula 32 as a specific example.

[0068] [Chemical Formula 31] Li a31 Ni x31 Co y31 M 31 z31 O 2-b31 X b31 In chemical formula 31, 0.9≦a31≦1.2, 0.8≦x31<1, 0 <y31≦0.2、0≦z31≦0.2、0.9≦x31+y31+z31≦1.1、および0≦b31≦0.1であり、M 31 X is Al, B, Ba, Ca, Ce, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sn, Sr, Ta, Ti, V, W, Y, Zn, Zr, or a combination thereof, and X is F, P, S, or a combination thereof.

[0069] In chemical formula 31, 0.9 ≤ x 31 ≤ 0.99, 0.01 ≤ y 31 ≤ 0.1, and 0 ≤ z 31 ≤ 0.1 may also be true.

[0070] [Chemical formula 32] Li a32 Ni x32 Co y32 M 32 z32 M 33 w32 O 2-b32 X b32 In chemical formula 32, 0.9≦a32≦1.2, 0.8≦x32≦0.98, 0.01≦y32≦0.19, 0.01≦z32≦0.19, 0≦w32≦0.19, 0.9≦x32+y32+z32+w32≦1.1, and 0≦b32≦0.1, M 32 is Al, Mn, or a combination thereof, M 33 These are B, Ba, Ca, Ce, Cr, Cu, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ta, Ti, V, W, Y, Zn, Zr, or combinations thereof, M 32 and M 33 These are all different elements, and X is F, P, S, or a combination of these.

[0071] In chemical formula 32, 0.9 ≤ x 32 ≤ 0.98, 0.01 ≤ y 32 ≤ 0.09, 0.01 ≤ z 32 ≤ 0.09, and 0 ≤ w 32 ≤ 0.09 may also be applied.

[0072] In the third lithium-nickel composite oxide, the nickel content may be 80 mol% or more with respect to 100 mol% of the metal excluding lithium, for example, 82 mol% or more, 85 mol% or more, 87 mol% or more, 90 mol% or more, or 91 mol% or more, or 99 mol% or less, for example, 95 mol% or less, and may be a high-nickel positive electrode active material. High-nickel positive electrode active materials can achieve high capacity and can be applied to high-capacity, high-density lithium secondary batteries.

[0073] In one embodiment of the positive electrode active material, the weight ratio (A:B) of the second positive electrode active material (A) to the third positive electrode active material (B) may be 1:10 to 10:1, for example, 1:9 to 9:1, 1:8 to 8:1, 1:7 to 7:1, 1:6 to 6:1, 1:5 to 5:1, 1:4 to 4:1, 1:3 to 3:1, or 1:2 to 2:1. When the weight ratio (A:B) of the second positive electrode active material (A) to the third positive electrode active material (B) satisfies the above range, the pellet density of the positive electrode active material increases, the principal stress decreases, and the powder fluidity can increase. On the other hand, when the weight ratio of the second positive electrode active material to the third positive electrode active material deviates from the above range, the pellet density may decrease and / or the principal stress may increase and / or the powder fluidity may decrease.

[0074] <Positive electrode> Another embodiment provides a positive electrode current collector and a positive electrode located on the positive electrode current collector and including a positive electrode active material layer containing the aforementioned positive electrode active material.

[0075] positive electrode current collector The positive electrode current collector is not particularly limited as long as it is conductive without inducing a chemical change in the lithium secondary battery, and may be aluminum foil or stainless steel foil with a thickness of 10 μm to 15 μm.

[0076] Cathode active material layer The positive electrode active material layer includes the aforementioned positive electrode active material.

[0077] The details regarding the positive electrode active material are as described above and will be omitted below.

[0078] The positive electrode active material may be present in amounts of 60% to 99.9% by weight, 70% to 99.8% by weight, 80% to 99.8% by weight, 90% to 99.8% by weight, 90% to 99.8% by weight, 90% to 99% by weight, or 90% to 98% by weight, relative to 100% by weight of the positive electrode active material layer.

[0079] The positive electrode active material layer may further selectively include a binder, a conductive material, or a combination thereof.

[0080] The binder plays a role in ensuring that the positive electrode active material particles adhere well to each other and that the positive electrode active material adheres well to the current collector. Typical examples of binders include, but are not limited to, polyvinyl alcohol, carboxymethylcellulose, hydroxypropylcellulose, diacetylcellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, epoxy resin, (meth)acrylic resin, polyester resin, and nylon.

[0081] The conductive material is used to impart conductivity to the electrodes, and any electronically conductive material that does not cause chemical changes can be used in the battery that is constructed. Examples of conductive materials include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjenblack, carbon fibers, carbon nanofibers, and carbon nanotubes; metallic materials containing copper, nickel, aluminum, silver, etc., in the form of metal powder or metal fiber; conductive polymers such as polyphenylene derivatives; or mixtures thereof.

[0082] In the positive electrode active material layer, the binder may be included in an amount of approximately 0.1% to 5% by weight relative to 100% by weight of the positive electrode active material layer, and the conductive material may be included in an amount of 0.1% to 5% by weight relative to 100% by weight of the positive electrode active material layer.

[0083] The loading level of the positive electrode active material layer is 10 mg / cm³. 2 ~30 mg / cm³ 2 It may be 10 mg / cm³, for example. 2 ~25 mg / cm³ 2 or 10 mg / cm³ 2 ~20 mg / cm³ 2 This may also be the case. Furthermore, in the final rolled positive electrode, the composite density of the positive electrode active material layer may be 3.75 g / cc to 4.0 g / cc, for example, 3.75 g / cc to 3.9 g / cc, or 3.75 g / cc to 3.85 g / cc. The positive electrode active material according to one embodiment is advantageous in achieving such loading levels and positive electrode active material layer densities, and a positive electrode satisfying the above-mentioned loading levels and composite density is advantageous in realizing a high-capacity, high-energy-density lithium secondary battery.

[0084] <Lithium-ion secondary battery> Another embodiment provides a lithium secondary battery comprising the positive electrode, negative electrode, and electrolyte described above. The lithium secondary battery may include a positive electrode, a negative electrode, a separator located between the positive and negative electrodes, and an electrolyte.

[0085] Lithium-ion batteries can be classified into cylindrical, prismatic, pouch-type, coin-type, and other types depending on their form. Figures 1 to 4 are schematic diagrams showing a lithium-ion battery according to one embodiment, where Figure 1 is cylindrical, Figure 2 is prismatic, and Figures 3 and 4 are pouch-type batteries. Referring to Figures 1 to 4, the lithium-ion battery 100 may include an electrode assembly 40 with a separator 30 interposed between a positive electrode 10 and a negative electrode 20, and a case 50 in which the electrode assembly 40 is housed. The positive electrode 10, negative electrode 20, and separator 30 may be impregnated with an electrolyte (not shown). The lithium-ion battery 100 may include a sealing member 60 that seals the case 50, as shown in Figure 1. Also, in Figure 2, the lithium-ion battery 100 may include a positive electrode lead tab 11 and a positive electrode terminal 12, a negative electrode lead tab 21 and a negative electrode terminal 22. As shown in Figures 3 and 4, the lithium secondary battery 100 may include electrode tabs 70, namely a positive electrode tab 71 and a negative electrode tab 72, which serve as electrical pathways for guiding the current formed in the electrode assembly 40 to the outside.

[0086] The specific details regarding the positive electrode included in the lithium secondary battery are as described above and will be omitted below. The lithium secondary battery according to one embodiment can significantly improve the electrical resistance of the electrode while ensuring excellent lifespan and rate characteristics by including the positive electrode described above.

[0087] negative electrode A negative electrode for a lithium secondary battery includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector. The negative electrode active material layer comprises a negative electrode active material and may further optionally include a binder, a conductive material, or a combination thereof.

[0088] The negative electrode current collector is not particularly limited as long as it is conductive without inducing a chemical change in the lithium secondary battery, and may be a copper foil with a thickness of 10 μm to 15 μm.

[0089] The negative active material includes a material capable of reversibly intercalating / deintercalating lithium ions, lithium metal, an alloy of lithium metal, a material capable of being doped and dedoped with lithium, or a transition metal oxide.

[0090] The material capable of reversibly intercalating / deintercalating lithium ions is a carbon-based negative active material, which may include, for example, crystalline carbon, amorphous carbon, or a combination thereof. Examples of the crystalline carbon include graphite such as amorphous, plate-like, flake-like, spherical or fibrous natural graphite or artificial graphite, and examples of the amorphous carbon include soft carbon or hard carbon, mesophase pitch carbide, calcined coke, and the like.

[0091] As the lithium metal alloy, an alloy of lithium and a metal selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn can be used.

[0092] As the material capable of being doped and dedoped with lithium, a Si-based negative active material or a Sn-based negative active material can be used. The Si-based negative active material may be silicon, a silicon-carbon composite, SiOx (0<x≦2), a Si-Q alloy (where Q is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements (excluding Si), Group 15 elements, Group 16 elements, transition metals, rare earth elements, and combinations thereof, for example, selected from Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof), or a combination thereof. The Sn-based negative active material may be Sn, SnO₂, a Sn alloy, or a combination thereof.

[0093] The silicon-carbon composite may be a composite of silicon and amorphous carbon. The average particle size (D) of the silicon-carbon composite particles. 50 The thickness of the silicon-carbon composite may be, for example, 0.5 μm to 20 μm. According to one embodiment, the silicon-carbon composite may be in the form of silicon particles and amorphous carbon coated on the surface of the silicon particles. For example, it may include secondary particles (core particles) assembled from primary silicon particles and an amorphous carbon coating layer (shell) located on the surface of these secondary particles. The amorphous carbon may also be located between the primary silicon particles, for example, the primary silicon particles may be coated with amorphous carbon. The secondary particles may be dispersed in the amorphous carbon matrix.

[0094] The silicon-carbon composite may further contain crystalline carbon. For example, the silicon-carbon composite may include crystalline carbon and core particles containing silicon particles, and an amorphous carbon coating layer located on the surface of these core particles. The crystalline carbon may be artificial graphite, natural graphite, or a combination thereof. The amorphous carbon may be soft carbon or hard carbon, mesophase pitch carbide, calcined coke, and the like.

[0095] When the silicon-carbon composite contains silicon and amorphous carbon, the silicon content may be 10% to 50% by weight per 100% by weight of the silicon-carbon composite, and the amorphous carbon content may be 50% to 90% by weight. Furthermore, when the composite contains silicon, amorphous carbon, and crystalline carbon, the silicon content per 100% by weight of the silicon-carbon composite may be 10% to 50% by weight, the crystalline carbon content may be 10% to 70% by weight, and the amorphous carbon content may be 20% to 40% by weight.

[0096] Furthermore, the thickness of the amorphous carbon coating layer may be 5 nm to 100 nm. The average particle size (D) of the silicon particles (primary particles) 50) may be 10 nm to 1 μm, or 10 nm to 200 nm. The silicon particles may exist as silicon alone, in a silicon alloy form, or in an oxidized form. The oxidized form of silicon can be SiO x (0<x≦2). At this time, the atomic content ratio of Si:O indicating the oxidation degree may be 99:1 to 33:67. In the present specification, unless otherwise defined, the average particle diameter (D 50 ) means the diameter of particles at a cumulative volume of 50% by volume in the particle size distribution.

[0097] The Si-based negative electrode active material or Sn-based negative electrode active material may be used in admixture with a carbon-based negative electrode active material. When the Si-based negative electrode active material or Sn-based negative electrode active material and the carbon-based negative electrode active material are used in admixture, the mixing ratio by weight may be 1:99 to 90:10.

[0098] The negative electrode active material may be included in an amount of 90 wt% to 99.8 wt%, or 94 wt% to 99 wt%, based on 100 wt% of the negative electrode active material layer.

[0099] The binder serves to adhere the negative electrode active material particles well to each other, and also to adhere the negative electrode active material well to the current collector. As the binder, a non-aqueous binder, an aqueous binder, a dry binder, or a combination thereof may be used.

[0100] Examples of the non-aqueous binder include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene-propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyimide, or a combination thereof.

[0101] The aqueous binder may be selected from styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinylpyrrolidone, polyepichlorohydrin, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, and combinations thereof.

[0102] When an aqueous binder is used as the negative electrode binder, it may further contain a cellulosic compound that can impart viscosity. This cellulosic compound can be a mixture of one or more carboxymethylcellulose, hydroxypropylmethylcellulose, methylcellulose, or alkali metal salts thereof. The alkali metal can be Na, K, or Li.

[0103] The dry binder is a polymeric substance that can be formed into fibers, and may be, for example, polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or a combination thereof.

[0104] The conductive material is used to impart conductivity to the electrodes, and any electronically conductive material that does not cause chemical changes can be used in the battery that is constructed. Specific examples include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjenblack, carbon fibers, carbon nanofibers, and carbon nanotubes; metallic materials in the form of metal powders or metal fibers containing copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or mixtures thereof.

[0105] The content of the binder may be 0.1% to 5% by weight relative to 100% by weight of the negative electrode active material layer, and the content of the conductive material may be 0.1% to 5% by weight relative to 100% by weight of the negative electrode active material layer.

[0106] electrolyte The electrolyte for lithium secondary batteries may be, for example, an electrolyte solution, which contains a non-aqueous organic solvent and a lithium salt.

[0107] The non-aqueous organic solvent acts as a medium through which ions involved in the electrochemical reaction of the battery can move. The non-aqueous organic solvent may be a carbonate, ester, ether, ketone, or alcohol, an aprotic solvent, or a combination thereof.

[0108] Examples of carbonate-based solvents that can be used include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate (BC). Examples of ester-based solvents that can be used include methyl acetate, ethyl acetate, n-propyl acetate, t-butyl acetate, methyl propionate, ethyl propionate, decanolide, mevalonolactone, valerolactone, and caprolactone. As ether-based solvents, dibutyl ether, tetraglyme, diglyme, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, and tetrahydrofuran can be used. As ketone-based solvents, cyclohexanone can be used. As alcohol-based solvents, ethyl alcohol and isopropyl alcohol can be used, and as aprotic solvents, nitriles such as R-CN (where R is a linear, branched, or cyclic hydrocarbon group with 2 to 20 carbon atoms, and can include double bonds, aromatic rings, or ether groups); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane and 1,4-dioxolane; and sulfolanes can be used.

[0109] Non-aqueous organic solvents can be used alone or in combination of two or more, and the mixing ratio when using two or more can be appropriately adjusted according to the desired battery performance, which is widely understood by those working in the field.

[0110] When using carbonate-based solvents, cyclic carbonates and linear carbonates can be mixed, and these can be mixed in a volume ratio of 1:1 to 1:9.

[0111] The non-aqueous organic solvent may further contain an aromatic hydrocarbon organic solvent. For example, the carbonate solvent and the aromatic hydrocarbon organic solvent can be mixed and used in a volume ratio of 1:1 to 30:1.

[0112] The electrolyte may further contain vinyl ethyl carbonate, vinylene carbonate, or ethylene carbonate compounds to improve battery life.

[0113] Typical examples of the aforementioned ethylene carbonate compounds include fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, and cyanoethylene carbonate.

[0114] Lithium salts are substances that dissolve in non-aqueous organic solvents and act as a source of lithium ions in batteries, enabling the operation of basic lithium secondary batteries and facilitating the movement of lithium ions between the positive and negative electrodes. Typical examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO2C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), LiC4F9SO3, and LiN(C x F 2x+1 SO2)(C y F 2y+1 It may contain one or more selected from SO2) (where x and y are integers from 1 to 20), lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluorobis(oxalate)phosphate (LiDFBOP), and lithium bis(oxalate) borate (LiBOB).

[0115] The lithium salt concentration is preferably within the range of 0.1 M to 2.0 M. When the lithium salt concentration falls within this range, the electrolyte has appropriate ionic conductivity and viscosity, resulting in excellent performance and effective lithium ion movement.

[0116] Separator Depending on the type of lithium secondary battery, a separator may be present between the positive and negative electrodes. Such separators can be made of polyethylene, polypropylene, polyvinylidene fluoride, or multilayer films of two or more layers of these materials. Mixed multilayer films such as polyethylene / polypropylene two-layer separators, polyethylene / polypropylene / polyethylene three-layer separators, and polypropylene / polyethylene / polypropylene three-layer separators can also be used.

[0117] The separator may include a porous substrate and a coating layer comprising organic, inorganic, or a combination thereof located on one or both sides of the porous substrate.

[0118] The porous substrate may be a polymer film formed from one polymer selected from polyethylene, polyolefins such as polypropylene, polyesters such as polyethylene terephthalate and polybutylene terephthalate, polyacetal, polyamide, polyimide, polycarbonate, polyetherketone, polyaryletherketone, polyetherimide, polyamideimide, polybenzimidazole, polyethersulfone, polyphenylene oxide, cyclic olefin copolymer, polyphenylene sulfide, polyethylene naphthalate, and polytetrafluoroethylene (e.g., TEFLON®), or from a copolymer or mixture of two or more of these. The porous substrate may be formed from glass fibers, or from a film formed from a mixture of the polymer and glass fibers.

[0119] The porous substrate can have a thickness of approximately 1 μm to 40 μm, for example, 1 μm to 30 μm, 1 μm to 20 μm, 5 μm to 15 μm, or 10 μm to 15 μm.

[0120] The organic material may include a (meth)acrylic copolymer comprising a first structural unit derived from (meth)acrylamide, and a second structural unit comprising at least one of a structural unit derived from (meth)acrylic acid or (meth)acrylate and a structural unit derived from (meth)acrylamide sulfonic acid or a salt thereof.

[0121] The inorganic material may include, but is not limited to, inorganic particles of Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, GaO, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, boehmite, or combinations thereof. The average particle size (D 50 The wavelength range may be 1 nm to 2000 nm, for example, 100 nm to 1000 nm or 100 nm to 700 nm.

[0122] The organic and inorganic materials may exist mixed together in a single coating layer, or in a form in which a coating layer containing organic materials and a coating layer containing inorganic materials are laminated together.

[0123] The thickness of the coating layer may be 0.5 μm to 20 μm, for example, 1 μm to 10 μm, or 1 μm to 5 μm. [Examples]

[0124] Examples and comparative examples of the present invention are described below. However, the examples described below are merely one embodiment of the present invention, and the present invention is not limited to the examples described below.

[0125] Example 1 (1) Manufacturing of positive electrode active material This is a form of secondary particles formed by the aggregation of multiple primary particles, and the average particle size (D) of the secondary particles is 50 ) is 15 μm, Ni 0.916 Co 0.072 Mn 0.012 A nickel-based precursor (OH)2 and a lithium raw material (LiOH) are mixed so that the total number of moles of metal in the nickel-based precursor and the lithium in the lithium raw material are in a molar ratio of 1:1.05. The mixture is then heat-treated at 750°C for 10 hours under an oxygen atmosphere, resulting in a form of secondary particles in which multiple primary particles have aggregated, and the average particle size of the secondary particles is (D 50 ) is 15 μm, Li 1.05 Ni 0.916 Co 0.072 Mn 0.012 A first positive electrode active material containing O2 was manufactured.

[0126] It is in single-particle form, and the average particle size (D) of the single particle 50 ) is 7 μm, Ni 0.916 Co 0.072 Mn 0.012 A nickel-based precursor (OH)2 and a lithium raw material (LiOH) are mixed so that the total number of moles of metal in the nickel-based precursor and the lithium in the lithium raw material are in a molar ratio of 1:1.05. The mixture is then heat-treated at 730°C for 10 hours under an oxygen atmosphere to obtain the average particle size (D) of the single particles. 50 ) is 7 μm, Li 1.05 Ni 0.916 Co 0.072 Mn 0.012 A second positive electrode active material containing O2 was manufactured.

[0127] It is in single-particle form, and the average particle size (D) of the single particle 50 ) is 3 μm, Ni 0.916 Co 0.072 Mn 0.012 A nickel-based precursor (OH)2 and a lithium raw material (LiOH) are mixed so that the total number of moles of metal in the nickel-based precursor and the lithium in the lithium raw material are in a molar ratio of 1:1.05. The mixture is then heat-treated at 710°C for 10 hours under an oxygen atmosphere, and the average particle size of the single particles (D 50 ) is 3 μm, Li 1.05 Ni 0.916 Co 0.072 Mn 0.012A third positive electrode active material containing O2 was manufactured.

[0128] The first positive electrode active material, the second positive electrode active material, and the third positive electrode active material were mixed in a weight ratio of 70:5:25 to produce a positive electrode active material.

[0129] (2) Manufacturing of lithium secondary batteries The manufactured cathode active material, polyvinylidene fluoride as a binder, and carbon nanotubes as a conductive material were mixed in a weight ratio of 98.5:1:0.5 (cathode active material:binder:conductive material), and this mixture was dispersed in N-methylpyrrolidone as a solvent to produce a cathode active material layer slurry. This slurry was coated onto an aluminum thin film, dried, and rolled to produce the cathode.

[0130] A lithium secondary battery was manufactured using a conventional method, employing lithium metal counter electrodes as the positive and negative electrodes, polytetrafluoroethylene as the separator, and a solvent prepared by dissolving 1 M LiPF6 in a mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 3:7 as the electrolyte.

[0131] Examples 2-3 and Comparative Examples 1-6 Except for mixing the first, second, and third positive electrode active materials in the weight ratio of 70:5:25 (first positive electrode active material: second positive electrode active material: third positive electrode active material) as in Example 1, the positive electrode active material and lithium secondary battery were manufactured in substantially the same manner as in Example 1, except that they were mixed in the weight ratios listed in Table 1 below. [Table 1]

[0132] Evaluation Example 1: Pellet Density The pellet density of the positive electrode active material produced in Examples 1-3 and Comparative Examples 1-6 was measured as follows. 3g of positive electrode active material was placed in a pellet manufacturing mold and maintained at 5 tons for 30 seconds. The density was then calculated from the pellet thickness and mold diameter, and the results are shown in Table 2 below.

[0133] Evaluation Example 2: Powder Flowability and Principal Stress The powder fluidity and principal stress of the positive electrode active materials produced in Examples 1-3 and Comparative Examples 1-6 were measured as follows.

[0134] Using an FT4 Powder Rheometer (Freeman Technology), 200 ml of the obtained positive electrode active material was added to a 300 ml vessel. After fixing the vessel to the apparatus, the powder fluidity and principal stress were measured at 9 kPa while moving the blade counterclockwise at a speed of 100 mm / s. This measurement was performed a total of three times, and the average values ​​were calculated and shown in Table 2 below.

[0135] In this case, the powder flowability is defined as a flow function (FF) value calculated based on the flow resistance of powder particles generated when the blade passes through the powder layer. The flow function (FF) is defined as the value obtained by dividing the major principal stress (σ1) by the unconfined yield strength (σc) of the powder, as shown in Equation 1 below, and is a dimensionless value that indicates the flow characteristics of the powder. [Formula 1] FF = σ1 / σc Here, σ1 represents the major principal stress when the powder is in a compressed state, and σc represents the unconfined yield strength at which the powder begins to collapse without external constraints.

[0136] Evaluation Example 3: Combination Density The positive electrode active material layer slurry produced in Examples 1-3 and Comparative Examples 1-6 was coated onto an aluminum thin film, dried, and rolled at a pressure until the positive electrode broke or the positive electrode active material desorption occurred. The maximum composite density was measured, and the results are shown in Table 2 below.

[0137] Evaluation Example 4: Initial charge / discharge capacity and its efficiency The initial charge / discharge capacity and efficiency of the lithium secondary batteries manufactured in Examples 1-3 and Comparative Examples 1-6 were measured as follows.

[0138] Initial charge and discharge were performed at room temperature (25°C) with a constant current of 0.2C rate (C-rate) up to the upper voltage limit of 4.3V, and then discharged at a 0.2C rate down to the cutoff voltage of 3.0V. The initial charge and discharge efficiency was calculated using the following formula 2, and the results are shown in Table 2 below. [Formula 2] Efficiency [%] = [Initial discharge capacity / Initial charge capacity] × 100

[0139] Evaluation Example 5: Measurement of DC-IR (Direct Current Internal Resistance) The DC-IR of the lithium secondary batteries manufactured in Examples 1-3 and Comparative Examples 1-6 was measured as follows:

[0140] After the initial charge and discharge described above, the system was adjusted to discharge at a 0.2C rate (C-rate) for 2 hours and 30 minutes to reach a State of Charge (SOC) of 90% or 10%. This was followed by constant current discharge at a 3C rate for 10 seconds, then constant current discharge at a 0.2C rate for 10 seconds, and finally constant current discharge at a 3C rate for another 10 seconds.

[0141] The DC internal resistance (DC-IR, R=ΔV / ΔI) was calculated from the ratio of the average voltage change (ΔV) and average current change (ΔI) during constant current discharge at each C-rate, and the average of these values ​​was used as the measured value. The results are shown in Table 2 below. [Table 2]

[0142] conclusion Examples 1-3, which include large particles in secondary particle form (first positive electrode active material), medium particles in single particle form (second positive electrode active material), and small particles in single particle form (third positive electrode active material), with medium and small particles comprising more than 20% but less than 40% by weight based on the total weight of the positive electrode active material, showed superior pellet density of 3.6 g / cc or more compared to other comparative examples, a reduction in principal stress to 20 kPa or less, and further improvement in powder flowability to 4.2 or higher. This not only improved the initial charge / discharge capacity but also confirmed that the DC-IR at SOC 10% and SOC 90% was significantly lower, indicating improved resistance.

[0143] On the other hand, in the case of Comparative Examples 1 to 4, which contain large and small particles but no medium particles, or contain only large and medium particles but no small particles, the pellet density was lower than that of the Examples, the principal stress was significantly higher than that of the Examples, and the powder fluidity was at least twice as low, confirming that the powder fluidity was poor. Consequently, the initial charge / discharge capacity and its efficiency were also lower than that of the Examples, and the DC-IR at SOC 10% and SOC 90% was about twice as high as that of the Examples, confirming that the resistance aspect was significantly inferior.

[0144] In Comparative Examples 5 and 6, which contain large, medium, and small particles, but where the total content of medium and small particles is 20% or less by weight relative to the total weight of the positive electrode active material, or 40% or more by weight, it can be confirmed that pellet density, principal stress, and powder flowability are all further improved compared to the other comparative examples. However, pellet density, principal stress, and powder flowability are all inferior to the examples, and consequently, the initial charge / discharge capacity and its efficiency are also inferior. In particular, it can be confirmed that the DC-IR at SOC 10% and SOC 90% is about 1 time higher than that of the examples, indicating inferior resistance.

[0145] This process resulted in the inclusion of large, medium, and small particles with an average particle size within a specific range. By adjusting the content of these medium and small particles within a specific range relative to the total weight of the positive electrode active material, the pellet density, principal stress, and powder fluidity were improved, thereby confirming that the initial charge / discharge capacity, its efficiency, and resistance aspects were all improved.

[0146] Although preferred embodiments have been described in detail above, the scope of the present invention is not limited thereto, and various modifications and improvements by those skilled in the art using the basic concepts defined in the following claims also fall within the scope of the present invention. [Explanation of Symbols]

[0147] 100: Lithium-ion rechargeable battery 10: Positive electrode 11: Positive lead tab 12: Positive terminal 20: Negative electrode 21: Negative lead tab 22: Negative terminal 30: Separator 40: Electrode assembly 50: Case 60: Sealing member 70: Electrode Tab 71: Positive Tab 72: Negative electrode tab

Claims

1. Average particle size (D 50 ) has a diameter of 10 μm or more and 30 μm or less, and the first positive electrode active material contains a first lithium nickel-based composite oxide, Average particle size (D 50 ) is 5 μm or more and less than 10 μm, and the first positive electrode active material contains a second lithium nickel-based composite oxide, and Average particle size (D 50 The particle size is 0.1 μm or more and less than 5 μm, and the third positive electrode active material contains a third lithium nickel-based composite oxide. It is a positive electrode active material, The combined weight of the second positive electrode active material and the third positive electrode active material is more than 20% by weight and less than 40% by weight, based on the total weight of the positive electrode active material. The powder flow function (FF) of the positive electrode active material is 4.2 or higher. Cathode active material.

2. The positive electrode active material according to claim 1, wherein the pellet density of the positive electrode active material is 3.6 g / cc to 4 g / cc.

3. The positive electrode active material according to claim 1, wherein the principal stress of the positive electrode active material is 20 kPa or less.

4. The positive electrode active material according to claim 1, wherein the first positive electrode active material is in the form of secondary particles formed by the aggregation of a plurality of primary particles.

5. The positive electrode active material according to claim 1, wherein the second positive electrode active material is in single-particle form and the third positive electrode active material is in single-particle form.

6. The first lithium nickel-based composite oxide is represented by the following chemical formula 1, and is the positive electrode active material according to claim 1: [Chemical formula 1] Li a1 Ni x1 M 1 y1 M 2 z1 O 2-b1 X b1 In chemical formula 1, 0.9 ≤ a1 ≤ 1.8, 0.3 ≤ x1 ≤ 1, 0 ≤ y1 ≤ 0.7, 0 ≤ z1 ≤ 0.7, 0.9 ≤ x1 + y1 + z1 ≤ 1.1, and 0 ≤ b1 ≤ 0.1, M 1 and M 2 These are all distinct elements, each independently being Al, B, Ba, Ca, Ce, Co, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sn, Sr, Ta, Ti, V, W, Y, Zn, Zr, or a combination thereof, while X is F, P, S, or a combination thereof.

7. The second lithium nickel-based composite oxide is represented by the following chemical formula 2, and is the positive electrode active material according to claim 1: [Chemical formula 2] Li a2 Ni x2 M 3 y2 M 4 z2 O 2-b2 X b2 In chemical formula 2, 0.9 ≤ a² ≤ 1.8, 0.3 ≤ x² ≤ 1, 0 ≤ y² ≤ 0.7, 0 ≤ z² ≤ 0.7, 0.9 ≤ x² + y² + z² ≤ 1.1, and 0 ≤ b² ≤ 0.1, M 3 and M 4 These are all distinct elements, each independently being Al, B, Ba, Ca, Ce, Co, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sn, Sr, Ta, Ti, V, W, Y, Zn, Zr, or a combination thereof, while X is F, P, S, or a combination thereof.

8. The third lithium nickel-based composite oxide is represented by the following chemical formula 3, and is the positive electrode active material according to claim 1: [Chemical formula 3] Li a3 Ni x3 M 5 y3 M 6 z3 O 2-b3 X b3 In chemical formula 3, 0.9 ≤ a³ ≤ 1.8, 0.3 ≤ x³ ≤ 1, 0 ≤ y³ ≤ 0.7, 0 ≤ z³ ≤ 0.7, 0.9 ≤ x³ + y³ + z³ ≤ 1.1, and 0 ≤ b³ ≤ 0.1, M 5 and M 6 These are all distinct elements, each independently being Al, B, Ba, Ca, Ce, Co, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sn, Sr, Ta, Ti, V, W, Y, Zn, Zr, or a combination thereof, while X is F, P, S, or a combination thereof.

9. The positive electrode active material according to claim 1, wherein the nickel content in the first lithium nickel-based composite oxide is 80 mol% or more relative to 100 mol% of the metal excluding lithium.

10. The positive electrode active material according to claim 1, wherein in the second lithium nickel-based composite oxide, the nickel content relative to 100 mol% of the metal excluding lithium is 80 mol% or more.

11. The positive electrode active material according to claim 1, wherein the nickel content in the third lithium nickel-based composite oxide is 80 mol% or more relative to 100 mol% of the metal excluding lithium.

12. The positive electrode active material according to claim 1, wherein the first positive electrode active material is included in an amount exceeding 60% by weight but less than 80% by weight, based on the total weight of the positive electrode active material.

13. The positive electrode active material according to claim 1, wherein the weight ratio of the second positive electrode active material to the third positive electrode active material is 1:10 to 10:

1.

14. Positive electrode current collector, and Located on the positive electrode current collector, and comprising a positive electrode active material layer containing a positive electrode active material according to any one of claims 1 to 13, Positive electrode.

15. A lithium secondary battery comprising a positive electrode, a negative electrode, and an electrolyte according to claim 14.